Composite microbial cement with short repair period and strong impermeability, preparation method and application
By using composite microbial cement composed of compound bacterial solution and nutrient salts, combining highly active fermentation broth of Basil Pasteurium and low-fat pectin, a repair material with gel properties is formed, and the existing microbial cement repair cycle is solved. The long repair cycle and resistance of anti-aging microbial cement in existing microbial cement The problem of poor permeability has achieved a significant shortening of the repair cycle and a significant improvement in permeability.
Patent Information
- Application Number
- CN202411601064.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-11
AI Technical Summary
During the repair process, existing microbial cement has problems such as long repair cycle, poor anti-seepage performance and excessive construction cycle, which is difficult to meet the needs of rapid repair on site.
Compound microbial cement composed of compound bacterial fluid and nutrient salts is used to combine highly active basil fermentation broth and low-fat pectin to form a repair material with gel properties, significantly shortening the repair cycle and improving anti-seepage performance.
The repair cycle has been significantly shortened, and the repair cycle has been shortened from the original three days to only one day, and the anti-violet recovery rate has been improved from 56.2% to 118.4%, which has significantly improved the anti-violet performance and application flexibility of the material.
Smart Images

Figure CN119461916A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the cross-technical field of microbiology, civil engineering and material science, and in particular to a composite microbial cement with a short repair period and strong impermeability, a preparation method and an application thereof. Background Art
[0002] Reinforced concrete is one of the most commonly used materials in the global construction industry, but over time, microcracks may appear inside and on its surface due to factors such as external loads. These cracks weaken the mechanical properties of concrete, promote the penetration of water and chemicals, and accelerate structural decay. At present, research on concrete repair materials mainly focuses on three categories: inorganic repair materials, organic repair materials, and microbial repair materials. Although inorganic materials such as cement paste and cement mortar are widely used, they have disadvantages such as high brittleness and low bonding strength; while organic materials such as acrylates and epoxy resins are susceptible to contamination and aging. Microbial induced calcium carbonate precipitation (MICP) technology is a sustainable bioremediation method that can effectively repair cracks in concrete. The calcium carbonate product generated is called microbial cement, which represents a new generation of repair materials.
[0003] Biocement is environmentally friendly and cost-effective, with excellent mechanical properties and high strength. The use of low-viscosity and small-particle bacterial liquid and nutrient salts can effectively repair concrete microcracks and improve the physical and mechanical properties after repair. However, the long repair cycle, the need for repeated grouting, and poor tolerance to water environments make it challenging to use in practice.
[0004] The Chinese invention patent application "CN202211268805.5, A concrete surface repair and protection method based on microbial cement" discloses a concrete surface repair and protection method based on microbial cement. This method adds viscose protein to the bacterial liquid to increase the toughness of the concrete surface repair layer and improve its crack resistance. However, the activity of the bacteria used is too low, resulting in a repair cycle of up to 15 days, which does not meet the needs of rapid repair in on-site applications.
[0005] The Chinese invention patent application "CN202111436095.8, Sodium alginate-immobilized microorganisms concrete crack repair material and preparation method thereof" discloses a sodium alginate-immobilized microorganisms concrete crack repair material and a preparation method thereof. The method does not mention the content of the method in improving the anti-seepage performance of concrete structure cracks after repair.
[0006] Compared with the above patent, the preparation process of the present invention is more simplified, effectively overcoming the limitation of ordinary microbial cement that needs to be prepared and used immediately, thus avoiding the problem of too long construction period. The material not only has excellent anti-seepage performance, but also significantly shortens the repair period and has good potential for on-site application. Summary of the invention
[0007] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a composite microbial cement with a short repair period and strong impermeability, a preparation method and an application thereof.
[0008] The technical solution adopted by the present invention to solve its technical problem is:
[0009] A method for preparing a composite microbial cement with a short repair cycle and strong impermeability, wherein the composite microbial cement is composed of a composite bacterial solution and nutrient salts; the specific preparation steps are as follows:
[0010] S1 is configured with YE-MH pasteurian spore Sarcina medium;
[0011] S2 prepares a highly active pasteurian sporesarcinia fermentation broth;
[0012] S3 dissolves low-fat pectin in the fermentation liquid to form a composite bacterial liquid;
[0013] S4 prepares a nutrient salt solution;
[0014] S5: uniformly mix the composite bacterial solution and the nutrient salt solution and let it stand for ten minutes to obtain composite microbial cement.
[0015] Furthermore, the composition and content of the YE-MH pasteurian sporosarcina culture medium in S1 are: yeast extract 30-34 g / L, ammonium sulfate 8-12 g / L, MH broth 6-8 g / L; nickel chloride 200 mg-240 mg / L, the solvent is water; the pH value is adjusted to 8.4-9.1 with 6 mol / L NaOH, and sterilized at 121°C under high pressure for 20 minutes.
[0016] Furthermore, in S2, YE-MH pasteurian spore octahedralis culture medium is used for activation culture, and the activation culture conditions are 28-35°C, 180-220r / min, and shaking culture for 15-20h; according to the inoculum size of 2-5%, it is inoculated into YE-MH pasteurian spore octahedralis culture medium for expansion culture, and the conditions are 28-35°C, 180-220r / min, and shaking culture for 22-26h to obtain a highly active pasteurian spore octahedralis fermentation liquid.
[0017] Furthermore, the OD of the highly active pasteurian spore Sarcina fermentation broth is 600 At 8-15; urease activity (high activity includes high OD600 and high enzyme activity) is above 18-24 mM / min.
[0018] Furthermore, in S3, 0.5% to 1.5% of low-fat pectin by mass of the fermentation broth is added to the fermentation broth, and the mixture is stirred at 30 to 35° C. for 2 to 4 hours to completely dissolve the pectin and obtain a composite bacterial liquid.
[0019] Furthermore, when 0.5% to 1.5% of low-fat pectin by mass of the fermentation liquid is added to the fermentation liquid, for cracks in the concrete structure with a width ranging from 0 to 0.5 mm, 0.5% to 1% of low-fat pectin by mass of the fermentation liquid is added; and for cracks with a width between 0.5 and 1 mm, 1% to 1.5% of low-fat pectin by mass of the fermentation liquid is added.
[0020] Furthermore, the specific steps for preparing 100 ml of nutrient salt solution in S4 are: dissolving 20-25 g of calcium acetate solid and 8-10 g of urea in distilled water, and after they are completely dissolved, adding distilled water to the solution to a total volume of 100 ml, and finally obtaining a nutrient salt solution.
[0021] Furthermore, the specific steps of uniformly mixing the composite bacterial solution and the nutrient salt solution and letting them stand for ten minutes in S5 are: fully mixing the required volume of nutrient salt solution with an equal volume of the composite bacterial solution to ensure that the composite bacterial solution and the nutrient salt are in full contact and form a stable composite system; leaving the mixed solution at 30°C to 35°C for 8 to 10 minutes to promote the full activity of the microorganisms and finally form a composite microbial cement.
[0022] The composite microbial cement prepared by the preparation method described above has a short repair period and strong impermeability.
[0023] The application of the preparation method as described above in repairing cracks in concrete structures.
[0024] The advantages and positive effects achieved by the present invention are:
[0025] 1. The method of the present invention aims to effectively shorten the repair cycle of microbial cement and significantly improve the anti-seepage performance of the repaired material. Specifically, the method first cultivates Bacillus pasteurianus in a culture medium with a high nutrient matrix to obtain a highly active bacterial solution. Then, an appropriate amount of low-fat pectin powder is dissolved in the bacterial solution of Bacillus pasteurianus to ensure that the two are fully and evenly mixed. The introduction of pectin can not only increase the local concentration in the reaction system, but also interact with calcium ions to form a gel, thereby achieving a rapid and effective sealing effect and repairing cracks. As a renewable green material, the composite microbial cement of the present invention shows great potential for large-scale production and sustainable use, and effectively solves the problem of long cycle of ordinary microbial cement in the repair process. It is in line with the development trend of ecological and environmental protection, and therefore has broad application prospects and market value.
[0026] 2. The method of the present invention is a method with fast repair speed, simple process, strong anti-seepage ability and green environmental protection. The composite microbial cement prepared by the method is a composite microbial cement used for repairing cracks in concrete structures. The present invention is a method for preparing composite microbial cement based on MICP technology, calcium ions and low-fat pectin combined to form a gel property, so as to solve the problems existing in the current practical application of microbial cement.
[0027] 3. The preparation method of the present invention optimizes the culture medium to promote the growth of Bacillus pasteurii, and combines low-fat pectin with microbial induced calcium carbonate precipitation (MICP) technology. Compared with ordinary microbial cement, the repair cycle of the present invention is shortened from the original three days to only one day. This not only improves the engineering efficiency, but also reduces the construction cost, providing a more convenient and economical solution for the practical application of microbial cement. Compared with ordinary microbial cement, the anti-seepage recovery rate of the present invention is also increased from 56.2% to 118.4%. The composite microbial cement prepared by the present invention has the characteristic of maintaining a usable state within five days, thereby effectively overcoming the limitation that ordinary microbial cement needs to be prepared and used immediately, and significantly improving its application flexibility. Compared with ordinary concrete crack repair methods, the present invention not only shows strong convenience in operation, but also has excellent material compatibility and environmental protection advantages. The introduction of this new type of cement represents the progress of microbial cement towards more efficient and sustainable solutions in the field of building materials, and helps to promote the development of concrete repair technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 These are two parallel test images of using composite microbial cement to repair 0.3 mm concrete structure cracks in the present invention;
[0029] Figure 2 This is a graph showing the anti-seepage performance of the specimen after the composite microbial cement repair in the present invention is completed;
[0030] Figure 3 This is a comparison chart of the biological activities of the bacterial solution fermented using the YE-NH4 original culture medium and the bacterial solution fermented using the YE-MH pasteurian sporosarcina culture medium in the present invention;
[0031] Figure 4 It is a comparison chart of the repair speed of microbial cement and composite microbial cement in the present invention; wherein, the upper and lower figures in the first column are two parallel tests of ordinary microbial cement repair, and the upper and lower figures in the second column are two parallel tests of composite microbial cement repair;
[0032] Figure 5 This is a comparison chart of the anti-seepage performance of the test piece after the composite microbial cement and the high-permeability epoxy resin repair are completed in the present invention;
[0033] Figure 6This is a comparison chart of the anti-seepage performance of the test piece after the repair is completed using 1% low-fat pectin composite microbial cement and 1% xanthan gum composite microbial cement in the present invention;
[0034] Figure 7 It is a comparison chart of the reaction speed of the bacterial liquid fermented by using YE-NH4 original culture medium in the composite microbial cement of the present invention and the bacterial liquid fermented by using YE-MH pasteurian sporosarcina culture medium in the composite microbial cement; wherein the upper and lower figures in the first column are two parallel tests of the composite microbial cement fermented by using YE-MH pasteurian sporosarcina culture medium, and the upper and lower figures in the second column are two parallel tests of the composite microbial cement fermented by using YE-NH4 original culture medium. DETAILED DESCRIPTION
[0035] The present invention will be further described below in conjunction with the embodiments. The following embodiments are descriptive rather than restrictive, and the protection scope of the present invention cannot be limited by the following embodiments.
[0036] The various experimental operations involved in the specific embodiments are all routine techniques in the art. For parts not specially annotated in this document, ordinary technicians in the art can implement them by referring to various commonly used reference books, scientific and technological literature or related instructions, manuals, etc. before the filing date of this invention.
[0037] A method for preparing a composite microbial cement with a short repair cycle and strong impermeability, wherein the composite microbial cement is composed of a composite bacterial solution and nutrient salts; the specific preparation steps are as follows:
[0038] S1 is configured with YE-MH pasteurian spore Sarcina medium;
[0039] S2 prepares a highly active pasteurian sporesarcinia fermentation broth;
[0040] S3 dissolves low-fat pectin in the fermentation liquid to form a composite bacterial liquid;
[0041] S4 prepares a nutrient salt solution;
[0042] S5: uniformly mix the composite bacterial solution and the nutrient salt solution and let it stand for ten minutes to obtain composite microbial cement.
[0043] Preferably, the composition and content of the YE-MH pasteurian sporosarcina culture medium in S1 are: 30-34 g / L yeast extract, 8-12 g / L ammonium sulfate, 6-8 g / L MH broth; 200 mg-240 mg / L nickel chloride, and the solvent is water; the pH value is adjusted to 8.4-9.1 with 6 mol / L NaOH, and sterilized by high pressure at 121°C for 20 minutes.
[0044] Preferably, in S2, YE-MH pasteurian spore octahedralis culture medium is used for activation culture, and the activation culture conditions are 28-35°C, 180-220r / min, and shaking culture for 15-20h; 2-5% of the inoculum is inoculated into YE-MH pasteurian spore octahedralis culture medium for expansion culture, and the conditions are 28-35°C, 180-220r / min, and shaking culture for 22-26h to obtain a highly active pasteurian spore octahedralis fermentation liquid.
[0045] Preferably, the OD of the highly active Bacillus pasteurianus fermentation broth is 600 At 8-15; urease activity (high activity includes high OD600 and high enzyme activity) is above 18-24 mM / min.
[0046] Preferably, in S3, 0.5% to 1.5% of low-fat pectin by mass of the fermentation broth is added to the fermentation broth, and the mixture is stirred at 30 to 35° C. for 2 to 4 hours to completely dissolve the pectin and obtain a composite bacterial solution.
[0047] Preferably, when 0.5% to 1.5% of low-fat pectin by weight of the fermentation liquid is added to the fermentation liquid, for cracks in the concrete structure with a width ranging from 0 to 0.5 mm, 0.5% to 1% of low-fat pectin by weight of the fermentation liquid is added; and for cracks with a width between 0.5 and 1 mm, 1% to 1.5% of low-fat pectin by weight of the fermentation liquid is added.
[0048] Preferably, the specific steps for preparing 100 ml of nutrient salt solution in S4 are: dissolving 20-25 g of calcium acetate solid and 8-10 g of urea in distilled water, and after they are completely dissolved, adding distilled water to the solution to a total volume of 100 ml, and finally obtaining a nutrient salt solution.
[0049] Preferably, the specific steps of uniformly mixing the composite bacterial solution and the nutrient salt solution and letting them stand for ten minutes in S5 are: fully mixing the required volume of nutrient salt solution with an equal volume of the composite bacterial solution to ensure that the composite bacterial solution and the nutrient salt are in full contact and form a stable composite system; leaving the mixed solution at 30°C to 35°C for 8 to 10 minutes to promote the full activity of the microorganisms and finally form a composite microbial cement.
[0050] The composite microbial cement prepared by the preparation method described above has a short repair period and strong impermeability.
[0051] The application of the preparation method as described above in repairing cracks in concrete structures.
[0052] Specifically, the relevant preparation and detection are as follows:
[0053] Example 1
[0054] A configuration of a high-activity YE-MH pasteurian spore Sarcina culture medium:
[0055] The components and contents of the culture medium are: 32 g / L yeast extract, 10 g / L ammonium sulfate, 8 g / L MH broth and 240 mg / L nickel chloride, and the solvent is water. The pH value of the culture medium is adjusted to 9.0 by 6 mol / L sodium hydroxide, and sterilized in a high pressure steam sterilizer at 121°C for 20 minutes.
[0056] Cultivation steps: ① Use YE-MH pasteurian spore octahedralis culture medium for activation culture, the activation culture conditions are 30℃, 200r / min, and shaker culture for 18h; ② After the activation culture is completed, inoculate into YE-MH pasteurian spore octahedralis culture medium fermentation culture at a rate of 3% for expansion culture, the conditions are 30℃, 200r / min, and shaker culture for 24h to obtain highly active pasteurian spore octahedralis fermentation liquid. Use ultraviolet spectrophotometer to measure the concentration of the bacterial liquid, and after diluting 10 times, OD 600 The value range is above 8; the urease activity is determined by the conductivity method, and the determination steps are to take 1mL of bacterial liquid, add 9mL of 1.11mol / L urea solution, observe the conductivity change within 5 minutes, and the enzyme activity is measured to be above 18mM / min.
[0057] Example 2
[0058] A method for preparing a composite microbial cement with a short repair cycle and strong impermeability, wherein the composite microbial cement is composed of a composite bacterial solution and nutrient salts; the specific preparation steps are as follows:
[0059] ① 1% low-fat pectin by mass of the fermentation broth prepared in Example 1 was added to the highly active pasteurian sporesarcine fermentation broth prepared in Example 1, and then the temperature was set to 35°C in a constant temperature heating magnetic stirrer, and the speed was adjusted to 200 rpm for high-speed stirring for 3 hours until the low-fat pectin was completely dissolved, and finally a composite bacterial liquid with a concentration of 1% was obtained.
[0060] ② Dissolve 23g of calcium acetate solid and 9g of urea in distilled water. After they are completely dissolved, add distilled water to the solution to a total volume of 100ml, and finally obtain a nutrient salt solution with 1.5mol / L of calcium acetate and urea.
[0061] ③ The obtained composite bacterial solution and nutrient salt solution were uniformly mixed in a volume ratio of 1:1. After standing for 10 minutes in an environment of 30℃~35℃, the mixed solution was injected into the pre-prepared concrete cracks (the crack size was 80mm long, 200mm deep, and 0.3mm wide) using a syringe until the cracks were completely filled with the repair liquid.
[0062] ④ This repair operation is repeated every 3 hours, and a total of 3 repair operations are performed.
[0063] like Figure 1 As shown, after three repairs, the composite microbial cement successfully restored the integrity of the cracks, the filling material appeared yellow-white, and the repair effect was significant, which fully demonstrated the application potential of the composite microbial cement prepared by the present invention.
[0064] Example 3
[0065] Preparation and anti-seepage test of a composite microbial cement; the specific steps are:
[0066] ① 1% low-fat pectin by mass of the fermentation broth prepared in Example 1 was added to the highly active pasteurian sporesarcine fermentation broth prepared in Example 1, and then the temperature was set to 35°C in a constant temperature heating magnetic stirrer, and the speed was adjusted to 200 rpm for high-speed stirring for 3 hours until the low-fat pectin was completely dissolved, and finally a composite bacterial liquid with a concentration of 1% was obtained.
[0067] ② Dissolve 23g of calcium acetate solid and 9g of urea in distilled water. After they are completely dissolved, add distilled water to the solution to a total volume of 100ml, and finally obtain a nutrient salt solution with 1.5mol / L of calcium acetate and urea.
[0068] ③ The obtained composite bacterial solution and nutrient salt solution were uniformly mixed in a volume ratio of 1:1. After standing for 10 minutes in an environment of 30℃~35℃, the mixed solution was injected into the pre-prepared concrete cracks (the crack size was 80mm long, 200mm deep, and 0.3mm wide) using a syringe until the cracks were completely filled with the repair liquid.
[0069] ④ This repair operation is repeated every 3 hours, and a total of 3 repair operations are performed.
[0070] ⑤ The anti-seepage test method is used for testing. The specific test steps are as follows: After waxing the surrounding areas of the test piece and the unrepaired experimental area, record its mass as M1, then turn the repaired surface upside down and soak it in water, take it out at different time periods, quickly absorb the surface moisture with a wet towel and weigh it immediately, record it as M2, take the unrepaired crack specimen as the blank group and the intact specimen as the control group, and calculate its water absorption rate E and anti-seepage recovery rate (%) as follows:
[0071] E = (M2 - M1) / M1 x 100%.
[0072] Anti-seepage recovery rate (%) = E1 / E0×100%
[0073] Where: E0 represents the water absorption rate of the specimen after crack repair, %;
[0074] E1 represents the water absorption of the complete specimen, %.
[0075] The test results are as follows Figure 2 As shown. After the anti-seepage test, the anti-seepage recovery rate of the repaired specimen reached 118.39%, and its water absorption was 0.23ml, while the water absorption of the intact specimen was 0.27ml, and the water absorption of the unrepaired specimen was as high as 0.82ml. These data show that after the repair treatment of the present invention, the anti-seepage performance of the specimen has been significantly improved.
[0076] Comparative Example 1
[0077] This comparative example involves comparing the activity of a high-activity pasteurian spore octahedralis fermentation broth fermented with YE-MH medium and a pasteurian spore octahedralis fermented with YE-NH4 original medium. The components and contents of the YE-NH4 original medium are: 20 g / L yeast extract, 10 g / L ammonium sulfate, 0.13 mol / L Tris, water as solvent, and HCl to adjust the pH value to 9; the culture conditions of the YE-NH4 original medium fermentation broth are: 30°C, 200 r / min shaking culture for 24 hours. Figure 3 As shown, by comparing the activity of the highly active pasteurian spore octahedralis fermentation broth in Example 1 with the pasteurian spore octahedralis fermentation broth fermented from the original culture medium, it was found that the OD of the former was 600 The value was significantly increased to 12-15, compared with the OD of the original culture medium. 600 In addition, the urease activity was also significantly enhanced, reaching 20-24 mM / min, while the urease activity of the original culture medium was only 12-15 mmol·min -1 , the improvement also reached two times. Therefore, it can be seen that the culture medium is optimized, and the bacterial solution fermented by the optimized culture medium is better than the bacterial solution fermented by the original culture medium. The bacterial solution cultured by the high-activity culture medium has higher OD600 and enzyme activity than the original culture medium. The bacterial solution with high OD600 and high enzyme activity is more conducive to subsequent rapid repair.
[0078] Comparative Example 2
[0079] This comparative example involves comparing the repair speed of composite microbial cement and microbial cement repair materials. The preparation and repair steps of microbial cement are as follows:
[0080] ① Preparing a highly active pasteurian sporesarcine fermentation broth (same as in Example 1);
[0081] ② Dissolve 23g of calcium acetate solid and 9g of urea in distilled water. After they are completely dissolved, add distilled water to the solution to a total volume of 100ml, and finally obtain a nutrient salt solution with 1.5mol / L of calcium acetate and urea;
[0082] ③ Mix the bacterial solution and nutrient salt in a volume ratio of 1:1 and let it stand for 10 minutes;
[0083] ④Use a syringe to inject the evenly mixed liquid into the crack;
[0084] ⑤ Repeat the repair process three times with an interval of 3 hours. Then, compare the repaired specimen with the repaired specimen in Example 2. Figure 4 As shown, the results show that the composite microbial cement completed the repair with no cracks on the surface, while the microbial cement failed to achieve repair.
[0085] Comparative Example 3
[0086] This comparative example involves comparing the impermeability of composite microbial cement and high permeability epoxy resin repair material. The high permeability epoxy resin repair steps are as follows:
[0087] ① Evenly mix epoxy resin material A and amino hardener polyamide resin B in a mass ratio of 4:1;
[0088] ② Use a syringe to inject the mixed solution into the crack until the overflow stops;
[0089] ③Repeat the repair process three times with an interval of 3 hours.
[0090] ④ After the repair is completed, the anti-seepage performance of the composite microbial cement (ie, Example 3) and the high permeability epoxy resin repair material repair specimens are compared. The specific test steps are as follows: After the surroundings of the test specimen and the unrepaired experimental area are sealed with wax, the mass is recorded as M1, and then the repaired surface is inverted to fully immerse it in water, taken out at different time periods, and the surface moisture is quickly absorbed with a wet towel and immediately weighed, recorded as M2, with the unrepaired crack specimen as the blank group and the intact specimen as the control group. The water absorption rate E and the anti-seepage recovery rate (%) are calculated as follows:
[0091] E = (M2 - M1) / M1 x 100%.
[0092] Anti-seepage recovery rate (%) = E1 / E0×100%
[0093] Where: E0 represents the water absorption rate of the specimen after crack repair, %;
[0094] E1 represents the water absorption of the complete specimen, %.
[0095] like Figure 5 As shown in the figure, the anti-seepage recovery rate of the specimens repaired with composite microbial cement reached 118.4%, which is significantly better than the 40.5% of high permeability epoxy resin material.
[0096] Comparative Example 4
[0097] In this comparative example, the low-fat pectin component in the composite microbial cement is replaced with xanthan gum, and the remaining steps are the same as those in Example 3. After the repair is completed, it is compared with Example 3; the specific steps are:
[0098] ① Add 1% xanthan gum by mass of the fermentation broth prepared in Example 1 to the highly active pasteurian sporesarcine fermentation broth prepared in Example 1, then set the temperature to 35°C in a constant temperature heating magnetic stirrer, and adjust the speed to 200 rpm for high-speed stirring for 3 hours until the xanthan gum is completely dissolved, and finally obtain a composite bacterial liquid with a concentration of 1%.
[0099] ② Dissolve 23g of calcium acetate solid and 9g of urea in distilled water. After they are completely dissolved, add distilled water to the solution to a total volume of 100ml, and finally obtain a nutrient salt solution with 1.5mol / L of calcium acetate and urea.
[0100] ③ The obtained composite bacterial solution and nutrient salt solution were uniformly mixed in a volume ratio of 1:1. After standing for 10 minutes in an environment of 30℃~35℃, the mixed solution was injected into the pre-prepared concrete cracks (the crack size was 80mm long, 200mm deep, and 0.3mm wide) using a syringe until the cracks were completely filled with the repair liquid.
[0101] ④ This repair operation is repeated every 3 hours, and a total of 3 repair operations are performed.
[0102] ⑤ The anti-seepage test method is used for testing. The specific test steps are as follows: After waxing the surrounding areas of the test piece and the unrepaired experimental area, record its mass as M1, then turn the repaired surface upside down and soak it in water, take it out at different time periods, quickly absorb the surface moisture with a wet towel and weigh it immediately, record it as M2, take the unrepaired crack specimen as the blank group and the intact specimen as the control group, and calculate its water absorption rate E and anti-seepage recovery rate (%) as follows:
[0103] E = (M2 - M1) / M1 x 100%.
[0104] Anti-seepage recovery rate (%) = E1 / E0×100%
[0105] Where: E0 represents the water absorption rate of the specimen after crack repair, %;
[0106] E1 represents the water absorption of the complete specimen, %.
[0107] like Figure 6As shown in the results, the anti-seepage recovery rate of the repaired specimens with 1% xanthan gum was 69.2%. In contrast, the anti-seepage recovery rate of the composite microbial cement with 1% low-fat pectin was significantly improved to 118.39%. This data shows that low-fat pectin is significantly better than xanthan gum in improving the anti-seepage performance of composite microbial cement.
[0108] Comparative Example 5
[0109] This comparative example involves comparing the reaction rates of a highly active pasteurian sporesarcine fermentation broth fermented using YE-MH medium and a pasteurian sporesarcine fermentation broth fermented using YE-NH4 medium. The components and contents of the YE-NH4 original medium are: 20 g / L yeast extract, 10 g / L ammonium sulfate, 0.13 mol / L Tris, the solvent is water, and the pH value is adjusted to 9 with HCl; the culture conditions of the YE-NH4 original medium fermentation broth are: 30°C, 200 r / min shaking culture for 24 hours.
[0110] ① The high-activity pasteurian spore octahedralis fermentation broth fermented in YE-MH medium prepared in Example 1 and the pasteurian spore octahedralis fermented in YE-MH4 medium with 1% low-fat pectin by weight were added to the two fermentation broths respectively, and then the temperature was set to 35°C in a constant temperature heating magnetic stirrer, and the speed was adjusted to 200 rpm for high-speed stirring for 3 hours until the low-fat pectin was completely dissolved, and finally two composite bacterial broths with a concentration of 1% were obtained.
[0111] ② Dissolve 23g of calcium acetate solid and 9g of urea in distilled water. After they are completely dissolved, add distilled water to the solution to a total volume of 100ml, and finally obtain a nutrient salt solution with 1.5mol / L of calcium acetate and urea;
[0112] ③ Thoroughly mix the two fermentation broths and nutrient salts in a volume ratio of 1:1 and let stand for 10 minutes;
[0113] ④Use a syringe to inject the evenly mixed liquid into the crack;
[0114] like Figure 7 As shown, the results show that under the same operating conditions, the bacterial solution cultured in YE-MH medium showed higher whiteness within 10 minutes, that is, its rate of producing calcium carbonate was significantly faster. The composite microbial cement using YE-NH4 medium to culture the bacterial solution did not show obvious white precipitation within 10 minutes. The experimental group had produced white precipitation in 10 minutes and started the repair process, while the control group had not yet started the repair. It can be seen that the composite microbial cement using YE-MH medium to ferment the bacterial solution has an advantage in repair speed.
[0115] At the same time, by comparing Examples 1-3 and Comparative Examples 4-5, it can be seen that the YE-MH pasteurian sporosarcina culture medium and low-fat pectin in the method of the present invention have a synergistic effect, which can synergistically improve the repair speed, application range and anti-seepage performance of the microbial cement.
[0116] Experimental results:
[0117] according to Figure 3 The data showed that the pasteurian sporesarcina culture obtained by fermenting with the culture medium provided by the present invention exhibited higher biomass and enzyme activity, both of which were more than twice as high as those of the original culture medium. Figure 4 It shows that after three rounds of repair, the composite microbial cement successfully repaired the 0.3 mm concrete cracks, while the ordinary microbial cement still failed to achieve this repair effect. Figure 2 and Figure 5 The results show that the concrete specimens repaired with composite microbial cement have an anti-seepage recovery rate of 118.4%, which is significantly better than the 40.5% of high-permeability epoxy resin repair materials. Replacing low-fat pectin with xanthan gum reduces its anti-seepage performance by about 50%. This data also shows that low-fat pectin is significantly better than xanthan gum in improving the anti-seepage performance of composite microbial cement.
[0118] The present invention proposes a method for preparing composite microbial cement with a short repair cycle and strong impermeability, which effectively solves the shortcomings of ordinary microbial cement in terms of repair speed, application range and impermeability. This innovative technology lays a solid foundation for the future development of the field of concrete repair.
[0119] Although the embodiments of the present invention are disclosed for illustrative purposes, those skilled in the art will appreciate that various substitutions, changes and modifications are possible without departing from the spirit and scope of the present invention and the appended claims. Therefore, the scope of the present invention is not limited to the contents disclosed in the embodiments.
Claims
1. A method for preparing a composite microbial cement with a short repair cycle and strong impermeability, characterized in that: The composite microbial cement is composed of composite bacterial liquid and nutrient salts; the specific preparation steps are as follows: S1 is configured with YE-MH pasteurian spore Sarcina medium; S2 prepares a highly active pasteurian sporesarcinia fermentation broth; S3 dissolves low-fat pectin in the fermentation liquid to form a composite bacterial liquid; S4 prepares a nutrient salt solution; S5: uniformly mix the composite bacterial solution and the nutrient salt solution and let it stand for ten minutes to obtain composite microbial cement.
2. The preparation method according to claim 1, characterized in that: The composition and content of the YE-MH pasteurian sporosarcina culture medium in S1 are: yeast extract 30-34 g / L, ammonium sulfate 8-12 g / L, MH broth 6-8 g / L; nickel chloride 200 mg-240 mg / L, the solvent is water; the pH value is adjusted to 8.4-9.1 with NaOH for sterilization.
3. The preparation method according to claim 1, characterized in that: In S2, YE-MH pasteurian sporosarcina culture medium is used for activation culture, and the activation culture conditions are 28-35°C, 180-220r / min, and shaking culture for 15-20h; according to the inoculum amount of 2-5%, it is inoculated into YE-MH pasteurian sporosarcina culture medium for expansion culture, and the conditions are 28-35°C, 180-220r / min, and shaking culture for 22-26h to obtain a highly active pasteurian sporosarcina fermentation liquid.
4. The preparation method according to claim 1, characterized in that: The OD of the highly active pasteurian spore Sarcina fermentation broth 600 Above 8; urease activity is above 18mM / min.
5. The preparation method according to claim 1, characterized in that: In S3, 0.5% to 1.5% of low-fat pectin by weight of the fermentation liquid is added to the fermentation liquid, and the mixture is stirred at 30 to 35° C. for 2 to 4 hours to completely dissolve the pectin, thereby obtaining a composite bacterial liquid.
6. The preparation method according to claim 5, characterized in that: When 0.5% to 1.5% of low-fat pectin by weight of the fermentation liquid is added to the fermentation liquid, for cracks in the concrete structure with a width ranging from 0 to 0.5 mm, 0.5% to 1% of low-fat pectin by weight of the fermentation liquid is added; and for cracks with a width between 0.5 and 1 mm, 1% to 1.5% of low-fat pectin by weight of the fermentation liquid is added.
7. The preparation method according to claim 1, characterized in that: The specific steps of preparing 100 ml of nutrient salt solution in S4 are as follows: dissolving 20-25 g of calcium acetate solid and 8-10 g of urea in distilled water, and after they are completely dissolved, adding distilled water to the solution to a total volume of 100 ml, and finally obtaining a nutrient salt solution.
8. The preparation method according to claim 1, characterized in that: The specific steps of uniformly mixing the composite bacterial solution and the nutrient salt solution and letting them stand for ten minutes in S5 are: fully mixing the required volume of nutrient salt solution with an equal volume of the composite bacterial solution to ensure that the composite bacterial solution and the nutrient salt are in full contact and form a stable composite system; leaving the mixed solution to stand at 30°C to 35°C for 8 to 10 minutes to promote the full activity of the microorganisms and finally form composite microbial cement.
9. The composite microbial cement having a short repair period and strong impermeability prepared by the preparation method according to any one of claims 1 to 8.
10. Application of the preparation method according to any one of claims 1 to 8 in repairing cracks in concrete structures.
Citation Information
Patent Citations
Concrete crack repairing material with sodium alginate immobilized microorganisms and preparation method of concrete crack repairing material
CN114213153A
Concrete surface repairing and protecting method based on microbial cement
CN115838302A
Method for plugging cast-in-situ concrete slab or base-plate crack with microbe-sedimented calcium carbonate
CN104196131A
Sludge curing agent based on microorganisms and fly ash and method for strengthening sludge
CN109650685A
Sludge curing agent based on microorganisms and method for strengthening sludge
CN109650686A